PENGARUH JENIS KENDARAAN BERMOTOR TERHADAP PENINGKATAN KONSENTRASI NITROGEN DIOKSIDA (NO2) DI SEKITAR BUNDARAN DOLOG - Muhammad Agus Ainur Rosyid; Euis Nurul Hidayah; Farida Pulansari (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2021)
Bundaran Dolog is surrounded by traffic area, which is being susceptible for traffic jam in peak hours. Peoples, who has been living around Bundaran Dolog, has a high risk of respiratory issues due to being exposed by nitogen dioxide (NO2) emission from vehicles. This study aims is to know the effect of the vehicles volume to the NO2 emission at Bundaran Dolog. Sampling was taken at Pelangi Park and Jemur Gayungan settlement for 8 point sampling within 6 days. The volume of identified vehicles, including light (LV), heavy (HV), and motorcycle (MC), temperature, and air flow velocity have been measured. The results shows that Pelangi Park has the average of NO2 is 30.92 ug/m3, temperature is 30,2℃ , whileJemur gayungan settlement identify concentration of NO2 41,07 ug/m3, temperature is 30,7℃ . The strong relationship between variable of different vehicles volume, temperature, air flowrate and the increasing of NO2 emission has been concluded by using multiple linear regression.